Historical drought analysis based on precipitation index - Ong, Ming Guan (Nanyang Technological University, 2022)
With the uncertainty of climate change in recent years, the management of water resources has become increasingly important with respect to drought. Drought analysis provides a consistent framework for the intensity of drought in preparation of a prolongation or shortening of a drought period. In this report, Standard Precipitation Index (SPI) will be used for calculation over a 0.25° grid over the Western Peninsula of Malaysia, longitude of 103.375 to 104.125°E, and latitude of 1.375 to 6.625°N. Time scales of 1, 3, 6, 12 months can be computed out using the MATLAB software over the period of 1951 to 2007. The standardization format of normal and gamma statistics enables the quantitative comparison of drought occurrences at different time scales. Overall, the year 1974 and 2004 had the lowest SPI, suggesting signs of drought. Annual analysis is also narrowed down to specific cities that are more agricultural intensive. Further analysis includes the degree of wetness in each month on the calendar from January to December throughout the 57 years of data.